PACED BREATHING REDUCES BLOOD PRESSURE AND ARTERIAL STIFFNESS: IMPACT OF THE AUTONOMIC NERVOUS SYSTEM. (June 2018) - Faconti, L.; Farukh, B.; Boguslavskyi, A.; Chowienczyk, P.
Abstract : Objective: The autonomic nervous system (ANS) plays an important role in regulating blood pressure (BP), but its action on arterial stiffness (AS) is still a subject of debate. Device-guided paced breathing (DGB) has been proposed as a non-pharmacological strategy to control BP –via the effects on ANS – but its effect on AS are unknown. Therefore, we examined if DGB would affect AS in hypertensive (HT) subjects. Design and method: Brachial BP (OMRON-705IT, Omron Corporation, Kyoto, Japan), central BP (pulse-wave analysis of the radial artery, SphygmoCor, AtCor Medical, Sydney, Australia), AS (carotid-femoral pulse wave velocity (cfPWV), Sphygmocor) and ANS activity (high resolution heart rate variability (HRV) as log-ratio of low-frequency/high-frequency range (LF/HF), Schiller Medilog AR12plus, United States) were determined in HT subjects. All measurements were performed in supine position after 15 min of rest and subsequently repeated during supervised DGB therapy which slows breathing < 10 breaths/min. Results: 25 HT patients (11 male), age (mean ± SD) 47 ± 12 years, systolic BP (SBP) 142.8 ± 19.4 mmHg, diastolic BP (DBP) 86.6 ± 8.7 mmHg and heart rate (HR) 72.4 ± 12.5 bpm were recruited. DGB decreased LF/HF by 0.09 ± 0.12 (p < 0.05) and reduced both brachial (−10.19 ± 7.89 mmHg) and central (−8.47 ± 6.80 mmHg) SBP, DBP (−3.6 ± 3.0 mmHg for brachial, p < 0.01) as well as HR (−3.48 ± 6.25 bpm, p < 0.05). cfPWV decreased from 9.81 ± 1.66m/s to 8.66 ± 1.60m/s (p < 0.01) and bivariate correlation showed no associations with changes in SBP, DBP or mean BP (MBP) (ß = 0.117, 0.107, 0.216 respectively; all p > 0.1). Finally, using the regression coefficient from meta-analysis and the observed decrease in MBP, we calculated the predicted reduction of cfPWV attributed to reduction in BP to be = 0.48 m/s, less than 50% of the observed reduction 1.04 (95%CI 0.65, 1.28)m/s. Conclusions: DGB decreased central/brachial BP, an effect likely to be mediated by the reduction of sympathetic activity as indicated by HRV. Effects to reduce cfPWV were greater than those predicted from the change in BP suggesting that the ANS may play an independent role in modulating AS in HT subjects.